The Philippines' security outlook - Misalucha-Willoughby, Charmaine (2023)
While there are nascent indicators, the new Marcos administration has yet to demonstrate a clear strategy for dealing with the competitive dynamics between China and the US, implications of the war in Ukraine, and mounting economic challenges on the domestic front. This has clouded the security outlook for the Philippines.